Бонавентура Клембовcький і мистецька освіта - Сторчай, О. (Студії мистецтвознавчі, 2007)
This article on the basis of worked out archive (it is putting into scientific usage) and published materials considers such questions: 1. creative biography of the talanted painter and artist B. Klembowsky (1795-1888); brief characteristic of his painting education at Kremenets (Wolynsky) Lycce, Wilensky University, trip abroad. 2. teaching activity of the artist at St. Volodimyr University (1834-1839); 3. Characteristic of the University art collection; 4. Museum and art knowledge activity of B. Klembowsky; 5. teaching at the history-philologycal faculty of the antique art and mythology courses (briefly); 6) project of Kyiv school of painting and art (it supplements the characteristic of the artistic education in 30-th of the XIX-th century at Kyiv University).